The Deviations of a deaf child: Components of Syntax and Phonology (Case Study of a Deaf Child) - Yusri Yusri (ELTE Journal (English Languange Teaching and Education), 2018)
Abstract This study aims to determine the type of deviation of a deaf child in syntactic and phonological components. This research was conducted by qualitative descriptive approach with recording and observation technique. The object of the study was a child with hearing impairment named Andini a grade 2 student of junior high school YPAC (Yayasan Pendidikan Anak Cacat) Karya Ibu in the academic year of 2016-2017, who was 15 years old, 95 decibels (db). Data obtained through observation and recording are described verbally through written language in sentence form. There are many language deviations or words uttered by Andini, a 15-year-old deaf girl. There are four types of language deviations in the phonological component: (1) Distortion, (2) substitution (3) omittion, And the last is (4) addition. In the syntactic component, of the 5 sentences uttered Andini there is no deviation in the syntactic component. But every word that Andini uttered in the sentence contains a language error in the phonological component.